The Test Re-Test Reliability of A Novel Single Leg Hop Test (T-Drill Hop Test) - Rodney Negrete; Samantha Simms; Jacob Gross; Lucas Nunes Rabello; Matt Hixon; Ibrahim M. Zeini; Walter L. Jenkins; George J. Davies (International Journal of Sports Physical Therapy)
# Background